Spatial Representation and Reasoning for Robot Mapping - Wolter, Diedrich (Springer, 2017)
This book addresses spatial representations and reasoning techniques for mobile robot mapping, providing an analysis of fundamental representations and processes involved. A spatial representation based on shape information is proposed and shape analysis techniques are developed to tackle the correspondence problem in robot mapping. A general mathematical formulation is presented to provide the formal ground for an efficient matching of configurations of objects.